2020
DOI: 10.1002/edm2.169
|View full text |Cite
|
Sign up to set email alerts
|

Comment on IWGDF ulcer prevention guidelines

Abstract: The IWGDF 2019 Updated Guidelines for prevention of foot ulcers in diabetes advise that nerve decompression surgery not be considered. This nerve decompression option has similar scientific supporting evidence to other surgeries which are recommended. The sanction ignores a large body of non‐Level 1 evidence demonstrating various beneficial outcomes of ND including pain relief, DFU prevention, and protection from recurrence and amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Peptic ulcers, upper gastrointestinal tumor, and acute gastric mucosal lesions were the most common [21]. This study showed that the most common causes of acute nonvaricose upper gastrointestinal bleeding were peptic ulcer, acute gastric mucosal lesion, and upper gastrointestinal tumor, and other causes were esophagocardiac mucosal tear syndrome [22]. The etiological distribution is similar to that reported in related studies.…”
Section: Discussionsupporting
confidence: 84%
“…Peptic ulcers, upper gastrointestinal tumor, and acute gastric mucosal lesions were the most common [21]. This study showed that the most common causes of acute nonvaricose upper gastrointestinal bleeding were peptic ulcer, acute gastric mucosal lesion, and upper gastrointestinal tumor, and other causes were esophagocardiac mucosal tear syndrome [22]. The etiological distribution is similar to that reported in related studies.…”
Section: Discussionsupporting
confidence: 84%
“…DFU refers to foot infections, epidermal wounds or tissue damage caused by aberrant nerve conduction velocity and reflex and varying degrees of vascular lesions in the distal lower extremity 5,6 . Evidently, its pathophysiology involves ulceration and profound tissue destruction caused by lower limb ischemic peripheral vascular disease, peripheral neuropathy and infection, which often requires amputation surgery due to osteomyelitis 5,6 . The deterioration of DFUs is responsible for more than 85% of amputations in diabetic individuals 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Evidently, its pathophysiology involves ulceration and profound tissue destruction caused by lower limb ischemic peripheral vascular disease, peripheral neuropathy and infection, which often requires amputation surgery due to osteomyelitis. 5 , 6 The deterioration of DFUs is responsible for more than 85% of amputations in diabetic individuals. 7 , 8 , 9 Of DFUs, ~50% or more become infected, wherein 20% of moderate‐to‐severe infections result in lower extremity amputation.…”
Section: Introductionmentioning
confidence: 99%